ANALISIS POTENSI BAHAYA DAN PENGENDALIAN BAHAYA MENGGUNAKAN METODE JOB SAFETY ANALYSIS (JSA) PADA PEKERJAAN TIRE CHANGER DI BENGKEL TEKNIK OTOMOTIF SMK MA'ARIF 1 WATES - Habib Rizqi Gymnastiar (Journal of Automotive Technology and Education, 2026)
This study aims to: (1) identify potential hazards in the tire changer work process at the automotive workshop of SMK Ma'arif 1 Wates, and (2) determine risk control measures for occupational accidents occurring during tire changer operations. This study employs the Job Safety Analysis (JSA) method, which systematically analyzes each step of the work process. The research adopts a qualitative descriptive approach, with data collected through direct observation and documentation. The results show that: (1) a total of 20 work steps were identified, involving 58 potential hazards; (2) the most dominant hazards were found in the processes of removing the tire from the rim and installing the new tire; (3) the most common hazard types included mechanical, ergonomic, and physical hazards such as pinching, falling objects, slipping, and injuries due to non-ergonomic postures; (4) the risk analysis produced 88 control recommendations consisting of administrative controls, engineering controls, substitution, and use of personal protective equipment (PPE); and (5) administrative control emerged as the dominant method for reducing risks across all work stages.